2021
DOI: 10.1002/oca.2803
|View full text |Cite
|
Sign up to set email alerts
|

Gear‐shifting control of non‐synchronizer electric‐driven mechanical transmission with active angle alignment

Abstract: Non‐synchronizer electric‐driven mechanical transmission (EMT) has advantages of low cost and simple mechanical structure, which is a key assembly in electric vehicles. In such an system, as the synchronizer is removed from the mechanical transmission, big impacts between the sleeve and clutch gear arise during a gear shift, which cause a long power‐off interruption. In this article, our contribution is to propose a novel control strategy to avoid impacts by achieving both zero relative rotational speed and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Recent research has extensively explored active angle alignment control as a means of synchronizing the speed of the sleeve with that of the target gear through coordinated regulation of the shift actuator and drive motor [19][20][21]. This approach aims to minimize shift time and mitigate impact during shifting [6,14,22]. As a result of the precise control of the engagement of the sleeve with the target gear, the teeth of the sleeve can smoothly enter the tooth groove of the gear ring without any collision, thereby achieving a shifting process characterized by minimal impact and zero tooth collision.…”
Section: Survey Of Amt Shift Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research has extensively explored active angle alignment control as a means of synchronizing the speed of the sleeve with that of the target gear through coordinated regulation of the shift actuator and drive motor [19][20][21]. This approach aims to minimize shift time and mitigate impact during shifting [6,14,22]. As a result of the precise control of the engagement of the sleeve with the target gear, the teeth of the sleeve can smoothly enter the tooth groove of the gear ring without any collision, thereby achieving a shifting process characterized by minimal impact and zero tooth collision.…”
Section: Survey Of Amt Shift Controlmentioning
confidence: 99%
“…Simulation and bench test results demonstrate that this control method can effectively reduce shift duration and minimize maximum impact. The dynamic model of the shifting process was initially derived as a hybrid automaton (HA) model by Ziwang Lu et al [6,22]. Subsequently, utilizing the minimum principle of Pontryagin, they solved for the time-optimal control law of synchronous speed and angle to achieve zero speed and angle difference, thereby reducing shifting time.…”
Section: Survey Of Amt Shift Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…They used the CHA model to solve an optimal control problem, and the synthesized controller could reduce the meshing duration by 71.05% and reduce impact impulse by 85.72% compared to an existing controller. Lu [37] designed a control strategy for non-synchronizer electric-driven mechanical transmission (EMT). He developed a HA model for the gear shifting process and showed that the impacts could be avoided by achieving both zero relative rotational speed and zero angle differences between the sleeve and clutch gear.…”
Section: Introductionmentioning
confidence: 99%